Intertidal Death Assemblages as Proxies of Marine Biodiversity. An Example from Northern Patagonia, Argentina. - Archuby, Fernando Miguel (2020)
Fil: Archuby, Fernando Miguel. Universidad Nacional de Río Negro, Instituto de Investigación en Paleobiología y Geología. Río Negro; Argentina.